E EFEKTIFTAS POHON LITERASI HIDUP UNTUK MENINGKATKAN KEMAMPUAN LITERASI SEKOLAH DASAR - cantika marsya; mirnawati; Niza yuliani; Muslimah; Syafrudin Muhdar (STKIP Subang, 2026)
This study aims to determine the effectiveness of the Living Literacy Tree media in improving the literacy skills of elementary school students. Literacy skills are essential competencies that students must possess because they are related to the ability to read, write, understand information, and convey ideas appropriately. However, low reading interest and the lack of engaging learning media remain obstacles in literacy learning at the elementary school level. This study employed a qualitative approach with a descriptive research design. Data were collected through observations, interviews, and documentation involving teachers and elementary school students. In addition, the study was supported by literature reviews from various relevant scientific sources. The results showed that the use of the Living Literacy Tree was able to increase students’ participation in reading and writing activities, foster reading interest, and help students better understand reading materials. This media also created a more active, creative, and enjoyable learning atmosphere because students were able to display their literacy work in the classroom. Besides improving literacy skills, the Living Literacy Tree also helped develop students’ critical thinking skills and cooperation. Therefore, the Living Literacy Tree can be considered an effective alternative learning media to support literacy activities in elementary schools.